2011
DOI: 10.1016/j.fcr.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping and quantitative trait locus analysis of resistance to sterility mosaic disease in pigeonpea [Cajanus cajan (L.) Millsp.]

Abstract: a b s t r a c tSterility mosaic disease (SMD), considered as the "green plague of pigeonpea" and caused by pigeonpea sterility mosaic virus (PPSMV) is one of the major biotic factors, which leads to heavy yield losses and hence poses a big challenge for pigeonpea production in the Indian subcontinent. Variability in the sterility mosaic pathogen revealed the occurrence of five different isolates in India. Among them, three distinct SMD isolates have been characterized, viz., Patancheru, Bangalore and Coimbator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 31 publications
4
65
2
Order By: Relevance
“…Subsequently SSR marker-based genetic map was developed by Bohra et al (2011). Soon after this, intra-specific genetic maps were also generated using SSR markers with relatively very low marker density (Gnanesh et al 2011; Bohra et al 2012). SNP-based genotyping assays were also deployed for genetic map construction using inter-specific (Saxena et al 2012) and intra-specific mapping populations (Kumawat et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently SSR marker-based genetic map was developed by Bohra et al (2011). Soon after this, intra-specific genetic maps were also generated using SSR markers with relatively very low marker density (Gnanesh et al 2011; Bohra et al 2012). SNP-based genotyping assays were also deployed for genetic map construction using inter-specific (Saxena et al 2012) and intra-specific mapping populations (Kumawat et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, limited numbers of markers were available for genetic mapping which in turn resulted in producing very low density genetic maps in cultivated pigeonpea 6, 9 . For instance, the number of SSR markers in individual component genetic maps ranged from 59 to 140 while the consensus map constructed using six component maps had only 339 markers 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Saxena (2008) proposed that, genetics of PSMD depend on the resistance source, PSMV isolates and scoring methods and hence the resistance to PSMD in pigeonpea appears to be complex. However, most of the studies have been reported as susceptibility is dominant and resistance to be under the control of recessive genes (Gnanesh et al, 2011 andGanapathy et al, 2012). These different inheritance patterns could be attributed to the difference in parents used for developing segregation population (Srinivas et al, 1997 andGanapathy et al, 2012) and different isolates used for screening (Srinivas et al, 1997).…”
Section: Resultsmentioning
confidence: 99%